2000
DOI: 10.1002/1521-186x(200101)22:1<46::aid-bem5>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Osmolality dependence of erythrocyte sedimentation and aggregation in a strong magnetic field

Abstract: In order to specify the major determinant of the magnetic enhancement of erythrocyte sedimentation observed previously, the dependence of erythrocyte sedimentation rate (ESR) on osmolality was measured under a strong magnetic field. Even at hypotonic osmolality, an increase in ESR due to aggregation was observed in plasma solution as compared with that without aggregation in saline solution. However, the magnetic field did not enhance ESR at hypotonic osmolality, when the cell shape was an isotropic sphere (sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 13 publications
0
5
0
1
Order By: Relevance
“…A previous study found that sedimentation and aggregation of erythrocytes increased when the erythrocytes were suspended in a plasma solution and exposed to a strong SMF with a magnetic induction of 6.3 T. However, this aggregative phenomenon disappeared when the cells were immersed in 20% hematocrit saline solution (Iino 1997, Iino andOkuda 2001). Th ese results provide evidence that the eff ect of an SMF on erythrocytes is strongly related to their surrounding solution.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study found that sedimentation and aggregation of erythrocytes increased when the erythrocytes were suspended in a plasma solution and exposed to a strong SMF with a magnetic induction of 6.3 T. However, this aggregative phenomenon disappeared when the cells were immersed in 20% hematocrit saline solution (Iino 1997, Iino andOkuda 2001). Th ese results provide evidence that the eff ect of an SMF on erythrocytes is strongly related to their surrounding solution.…”
Section: Discussionmentioning
confidence: 99%
“…ELF MFs, as well as heat shock, proved to increase microvescicle motility in astrocytes [82]. Both sedimentation and aggregation of erythrocytes were MF-dependent [83]. At the level of cell-cycle kinetics and at that of cell culture proliferation, there was an agreement regarding the MF-effect: variations of Friend erythroleukemia cell proliferation, following the addition or deprivation of MFs [84], were consistent either with alteration of the onset of S-phase established after a 50 Hz MF exposure of normal human fibroblasts [85] or with change of the growth and colony forming ability after exposure of budding yeast to 50 Hz MFs [86].…”
Section: Biotargets Of Middle Complexity Exhibited a Moderate Mf-stabmentioning
confidence: 78%
“…Erythrocytes thawed from the SMF-coupled freezing process used in this study exhibited no obvious cell aggregation (Figure 3). Previous studies showed that when erythrocytes were immersed in a normal saline solution with an Hct of 20%, the effect of an SMF on erythrocyte aggregation was slight, even when the cells were exposed to a strong SMF of up to 6.3 T [35], [36]. Additionally, ATP and 2,3-DPG metabolite tests were used to assess erythrocyte function after thawing [31].…”
Section: Discussionmentioning
confidence: 99%